Fostering Students’ Listening Comprehension Skill through Metacognitive Strategies Instructions: An Action Research Study - Rahma, Adillah Elifta; Anugerahwati, Mirjam (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study sought to provide a nuanced understanding of how can metacognitive strategies can be implemented for improving students’ listening comprehension skill of Eight graders students of Junior High School in Malang. This study employed Classroom Action Research in one cycle. This study was done in eight meetings, in which the preliminary and final tests were done in first and last meetings. Each meeting employed metacognitive strategies and Three-Phase Technique simultaneously; 1) Planning stage with Pre-listening phase, 2) Monitoring stage with Whilst-listening phase, and 3) Evaluating stage with Post-listening phase. The data gathered qualitatively through observation sheets, field notes, students’ interview, students’ questionnaire. The findings of this study found several trends of MSI that can improve students’ listening skill, namely strengthen students’ prior knowledge, incorporate process-based discussion, and the importance of teacher’s talk in MSI. However, Therefore, for further research in the same realm, it is urged to employ the results of this study as one of references in conducting research in similar field of the study. However, deeper evaluation concerning the findings of this study also need to be taken into account as this study could not be used as overgeneralization context as this study only use small sample.